In situ ammonia removal by methanogenic granular biomass. Issue 4 (28th February 2018) - Saha, Shaswati; De Vrieze, Jo; Biswas, Rima; Nandy, Tapas
Abstract : Ammonia-oxidizing bacteria and nitrite-oxidizing Nitropsira sp. and acetoclastic methanogens Methanosaeta sp. can co-exist together to simultaneously oxidise ammonia and generate methane. Abstract : Methanogenic granules from a sewage-fed 298 day old UASB reactor with a high abundance of Nitrospira sp. were evaluated for simultaneous methanogenesis and nitrification. Batch experiments were conducted under anaerobic and oxygen-limited conditions using either 0.04% (v/v) methanol (C) or ammonium chloride (30–100 mg N L −1 ) (N) or both (N + C). The results showed that C-utilization preceded N-utilization in the N + C sets, indicating that methanogenesis was independent of ammonia removal. Ammonia removal with nitrate generation under oxygen-limited conditions confirmed the nitrification potential of methanogenic granules. However, under anaerobic conditions, the decrease in the ammonium nitrogen concentration did not result in the stoichiometric increase in the nitrite & nitrate concentrations. Furthermore, hydrogenotrophic methanogens disappeared in the N and N + C sets. H2 -mediated denitrification could possibly be attributed to the disappearance of both nitrite or nitrate and hydrogenotrophic methanogens. An increase in the population of Methanosaetaceae compensated for methane production via the acetoclastic route. Thus, simultaneous nitrification & H2 -mediated denitrification was confirmed as the plausible route for ammonia removal in the methanogenic granules under anaerobic conditions. This finding of in situ ammonia removal in methanogens has opened new avenues for treating C/N wastewaters.